Case report of acute epiglottitis in a 44-year-old man: a rare case - I Gusti Ayu Putu Wahyu Widiantari; Nyoman Dian Permatasari; Ida Bagus Semara Putra (Intisari Sains Medis, 2021)
Background: Acute epiglottitis, also known as supraglottitis or supraglottic laryngitis, is an acute inflammation of the supraglottic area of the larynx. The diagnosis can be made based on clinical signs and symptoms as well as several investigations.Case Description: We reported a case of a 44-year-old man who presented to our emergency department and whose condition was ultimately diagnosed as epiglottitis. Indirect laryngoscopy and lateral soft tissue neck radiograph had an important role in determining the diagnosis. The patient was treated conservatively by giving a high dosed antibiotic, anti-inflammatory, and analgesic drugs.Conclusion: Acute epiglottitis can be a life-threatening condition because it can cause sudden upper airway obstruction. Therefore, management must be given quickly and precisely so as not to fall into a life-threatening condition.